Culture-Bound Syndromes of a Brazilian Amazon Riverine population: Tentative correspondence between traditional and conventional medicine terms and possible ethnopharmacological implications. (5th May 2017) - Pagani, E.; Santos, J. de F.L.; Rodrigues, E.
Abstract: Ethnopharmacological relevance: It is not always possible to correlate the "emic" terms to the "etic" ones during ethnopharmacological surveys, especially regarding those related to Culture-Bound Syndromes (CBS). Nevertheless, it is the role of ethnopharmacology to address these correlations, since they are the basis for the understanding of potential bioactives. Aim and objectives: This study reports the clinical manifestations and therapeutic resources used for the treatment of CBS among some riverine inhabitants of Brazilian Amazonia. An effort was made to establish a correspondence between the local "emic" terms of traditional medicine and the symptoms or diseases known by conventional medicine ("etic" terms). The ultimate goal was to gain insights to suggest further pharmacological studies with the local resources. Material and methods: Fieldwork was guided by methods of anthropology, botany and zoology—with the assistance of a doctor—among the traditional healing experts in Jaú National Park (during 199 days in 1995) and Unini River Extractive Reserve (210 days from 2008 to 2012). Results: Fifty-nine healers of different kinds were interviewed: a prayer-maker, medium, natural resource expert, massage therapist, midwife and snakebite healer. The clinical manifestations and healing resources of the following CBS were collected: "mau olhado" (evil eye), "quebrante" (chipping); "espante" (fright or susto ); "doença do ar" (air diseases); "vento caído" (fallen wind); "derrame" (leakage); "mãe do corpo" (mother of the body) and "panema" (unlucky). The first three seem to be local variations of other CBSs already described in Latin America. "doença do ar", "vento caído", "derrame" and "mãe do corpo" seem to be folk terms for known conventional medical disorders, while "panema" is a yet undescribed Brazilian CBS that is possibly related to dysthymic disorder or depression and deserves further investigation. Treatments included prayer rituals, fumigation, baths and oral remedies using 25 plants and 10 animals. Conclusion: It was possible to establish hypothetical correlations between CBS as described by the riverine population studied and some "etic" terms. The main importance of this is to help the proposition of target-oriented pharmacological studies of the natural resources used by these communities. Accordingly, the following plants are suggested to be submitted to further studies for antidepressant and anxiolytic activities: Siparuna guianensis, Mansoa alliacea, Leucas martinicensis, Petiveria alliacea, Annona montana and Alpinia nutans ; for anti-seizure activity: Protium amazonicum, Protium aracouchini and Protium heptaphyllum; finally for antispasmodic activity: Leucas martinicensis . Graphical abstract: